Searching for a bridge over troubled waters: An exploratory analysis of trust in United Kingdom fisheries management. (October 2021) - Ford, Eleanor; Stewart, Bryce D.
Abstract: Effective management of fisheries relies on high levels of trust between the fishing industry, managers and scientists. This study examines the current levels of trust that fishers have of governing and scientific bodies in United Kingdom (UK) fisheries, as the UK develops new management measures outside of the Common Fisheries Policy, after Brexit. A survey was conducted to examine trust, alongside fishers' opinions of current management goals and tools, and to investigate participation in cooperative schemes. We received a total of 43 responses from fishers across the UK representing a variety of vessel sizes and types of fisheries. These participants had low levels of trust in nearly all the institutions included in the survey, however, there was high variation between individual responses. The management goals of fishers aligned with several goals from Defra's 25-year Environment Plan. However, increasing the coverage of marine protected areas (MPAs) was the least popular goal. Increased use of selectivity devices was most favoured as a management tool, while MPAs were again the least popular. More encouragingly, those fishers who had previously collaborated with scientists and managers showed higher levels of trust across the board. Based on our results, we recommend increased use of fishing industry-science partnerships and co-management as key to increasing trust as the UK seeks to reform and improve its management of fisheries after Brexit. Although our sample size was relatively small, we hope our study paves the way for more expansive analyses into trust in fisheries sectors globally, and how it can be improved. Highlights: Participants had low levels of trust in nearly all of the UK fisheries related institutions. Protecting the seafloor and ensuring commercial sustainability were the most favoured goals. Increased use of selectivity devices was most favoured as a management tool. Increasing coverage of marine protected areas was the least popular environmental goal and the least popular management tool. Those fishers who had previously collaborated with scientists and managers showed higher levels of trust.